Innovative mechanisms for the development of local democracy - Рубан Дмитро Олександрович (My University, 2024)
The dissertation examines the current scientific problem of the development of local democracy through the use of innovative mechanisms and based on the analysis of scientific literature, regulatory documents, foreign and domestic experience, practical recommendations are proposed in the context of ensuring, on this basis, European integration and post-war recovery of Ukraine. As a result of the study, the theoretical foundations of the implementation of innovative mechanisms for the development of local democracy, aimed at continuing the processes of democratization and reforming the system of public administration in Ukraine, were revealed and deepened. Methodological approaches to monitoring local democracy have been systematized, on the basis of which the peculiarities of the Ukrainian and European model of democracy have been studied, trends in the development of local democracy and the content of decentralization reforms have been determined. The application of strategic, dynamic, integrated and complex approaches to the development of local democracy is substantiated; the key vectors of further reforms are given, which will ensure the creation of conditions for increasing the efficiency of local self-government through the use of innovative mechanisms for the development of local democracy. For the first time, mechanisms for the development of local democracy were developed and presented, taking into account the evolution of public management models (from the traditional model of public management to the concept of good governance), the need to use a multi-level approach to democratization reforms (local governance, regional governance, state governance, global governance), which made it possible to determine the elements of local democracy, to propose mechanisms for its development in the conditions of growing global challenges and wartime threats. In the first chapter of the dissertation work «Theoretical principles of managing the development of local democracy», the subject field of the study of the problem of the development of local democracy is formed - the process of transformation of the forms of interaction between the state and the citizen, which, through the improvement of principles, forms, mechanisms and tools, ensures an increase in the level of involvement of citizens in decision-making at all levels levels of public administration. On the basis of a comprehensive approach to the subject of research, the key characteristics and factors of democratization at various levels are systematized and the need to take them into account before the challenges and threats of wartime is substantiated. The development of the conceptual and categorical apparatus of the subject of the study was revealed and ensured: the author's interpretation of the concepts «democracy», «local democracy», «development of local democracy» was formulated. The role of local democracy in reforming the public administration system at various levels of public administration, as well as in the context of global governance and the implementation of the Sustainable Development Goals, is defined. The question of promoting the development of local democracy through decentralization on the part of international organizations has been studied. The provisions of the concept of the development of local democracy, which determine the functions of citizens and communities, procedures for discussing problems, political education, the effectiveness of government, territorial coordinates of activity, and the material and financial basis of activity, have been clarified. The essence of the mechanism of development of local democracy is revealed based on taking into account the targeted nature of use, complex structure, complex interaction of elements, dependence on conditions, dynamics of changes. Conceptual provisions for the functioning of effective mechanisms for the development of local democracy have been formed, which are considered as a set of algorithms for the implementation of procedures for the involvement of citizens in management, which are formed under the influence of legal, organizational, economic and social conditions, which in interaction provide a positive target result in the field of local democracy development - increase the influence civil society on the decisions made. The methods of monitoring local democracy are systematized, taking into account the need to study not only local democracy directly, but also the conditions of its development. Characteristics and examples of methods of measuring democracy in the country, methods of monitoring political systems, methods of monitoring democratic public administration and methods of analyzing local democracy are considered. The tools and goals of local democracy assessment have been clarified; the main areas of local management analysis are defined. The main attention is paid to the methods of measuring local democracy, which allows to investigate the democratic nature of local government, the strength and quality of local democracy, the level of use of e-technologies. An algorithm for multilevel analysis of the influence of democracy on economic processes has been developed. In the second chapter «System and mechanisms of development of local democracy in modern Ukraine» the issue of the development of local democracy in Ukraine is considered from the standpoint of using development mechanisms and taking into account foreign experience. The principles of managing the development of local democracy are proposed, which are justified on the basis of the systematization of relevant regulatory documents and principles of the European and international level, in particular the principles of transparency and accountability, efficiency and effectiveness, priority, convergence of interests and competence, which should be fully implemented in Ukraine, will allow use European experience in the development of democracy and strengthen Ukraine's position in the context of EU integration. The peculiarities of the development of local democracy in the context of democratization in the conditions of different types of regimes in the countries of the world, as well as models of local self-government, are revealed. A decrease in the level of development of democracy in Ukraine in 2022 in general and in terms of such components as the electoral process and pluralism, civil liberties, which was caused by the war, was noted. The declarative and fragmented character of the development of democracy in Ukraine is explained by the inconsistency of the reforms with the criteria of real democratization. Peculiarities of the decentralization process in different countries, which is the basis for the development of local self-government and the development of local democracy, have been studied. According to the models of sub-national governance (one-, two- and three-level) formed in the countries of the world as a result of decentralization, the distribution of state expenses is carried out. Arguments are presented regarding the influence of the level of decentralization on the economic development of the country, in particular on the level of capital expenditures, the use of which at the regional and local level ensures the implementation of investment projects related to the construction and reconstruction of infrastructure. Among the positive effects of decentralization in terms of the development of local democracy, it should be noted: increased transparency and accountability, ensuring the expansion of citizen participation in decision-making; a comparatively better level of taking into account the needs of citizens due to adequate resource provision. Democratization in Ukraine is taking place according to the option of a «delayed» transition, which was caused by the preservation of the negative characteristics of the previous model, a low level of motivation for systemic reforms of the political elites, and a low level of citizen involvement. Despite the implementation of a number of projects and initiatives of Ukrainian and international organizations regarding the development of local democracy, the spectrum of development tools has not gained proper distribution. The main challenges of the development of local democracy during the war are highlighted, including challenges of adaptation, migration and financial challenges, functional and bureaucratic challenges, challenges of sustainable development. The key limitation of the activities of territorial communities are losses: demographic, material, economic and financial. A positive result of the decentralization reforms is the high level of independence of local authorities in responding to the challenges of wartime, however, local democracy does not always have tools to counter corruption scandals and dishonest behavior of officials. In the third chapter «Promising directions of implementation of innovative mechanisms for the development of local democracy» it is proposed to use a strategic, dynamic, integrated and complex approach to the development of democracy, which will allow to form the conceptual basis of further reforms and will contribute to the creation of conditions for the implementation of innovative mechanisms of local democracy. The key directions of further reforms regarding the development of local democracy, taking into account the European and North Atlantic development vectors of Ukraine, the need to form drivers of economic growth in the regions, the tasks of further decentralization and the processes of inclusion in the global network of international organizations promoting democracy, the development of public organizations and civil society, have been determined. The conditions for the effective use of such mechanisms of local democracy as local elections, local referendum, public budget, and public hearings are substantiated. As a strategic reference point for the development of civil society in the context of the development of local democracy, a transition from the traditional paradigm of citizen involvement, which involves direct communication between the government and an individual citizen through such measures as public hearings, public «education», elections, surveys and written comments on proposals, is proposed . organizations contribute to the development of social and intellectual capital, institutional capacity and adaptability to changes in society as a whole. The purpose and components of the mechanisms of public participation in strengthening democracy at the national and local levels are substantiated. The purpose of the main forms of public involvement, including information, consultation, involvement, cooperation and empowerment, which together will create conditions for systemic interaction between the public and the government, has been determined. The advantages/disadvantages and conditions of using the following mechanisms of citizen participation are systematized: public advisory groups; municipal strategic planning; social monitoring; public-private partnership; public (public) meetings; management networks involving citizens. Among innovative mechanisms, it is proposed to use such mechanisms as a local action group, advisory mini-publics, community panels, public juries, open public spaces (hubs). The impact of digital transformations and information saturation of the activities of local self-government bodies on the effectiveness of management, which requires the use of new technologies, is studied. Artificial intelligence is a potentially important innovative tool for the transformation of public administration processes in the context of improving the effectiveness of local democracy. The positive and negative effects of the use of artificial intelligence in the process of local governance are summarized. The main areas of application of artificial intelligence in the process of development of local democracy, e-democracy and electronic governance are outlined. The practical significance of the obtained results lies in the development of recommendations for the implementation of innovative mechanisms for the development of local democracy in the context of ensuring the further democratization of Ukraine in accordance with the priorities of European integration.

У дисертаційній роботі досліджено актуальну наукову проблему щодо розвитку місцевої демократії через застосування інноваційних механізмів та на підставі аналізу наукової літератури, нормативно-правових документів, зарубіжного й вітчизняного досвіду, запропоновані практичні рекомендацій в контексті забезпечення, на цій основі, євроінтеграції та повоєнного відновлення України. В результаті дослідження розкрито та поглиблено теоретичні засади реалізації інноваційних механізмів розвитку місцевої демократії, спрямованих на продовження процесів демократизації та реформування системи публічного управління в Україні. Систематизовано методологічні підходи до моніторингу місцевої демократії, на основі яких досліджено особливості української та європейської моделі демократії, визначено тенденції розвитку місцевої демократії та зміст реформ з децентралізації. Обґрунтовано застосування стратегічного, динамічного, інтегрованого та комплексного підходів до розвитку місцевої демократії; наведено ключові вектори подальших реформ, які забезпечать створення умов для підвищення ефективності місцевого самоврядування за рахунок застосування інноваційних механізмів розвитку місцевої демократії. Уперше розроблено та представлено механізми розвитку місцевої демократії з урахуванням еволюції моделей публічного управління (від традиційної моделі публічного управління до концепції належного урядування), необхідності використання багаторівневого підходу до проведення реформ з демократизації (місцеве управління, регіональне управління, державне управління, глобальне управління), що дозволило визначити елементи місцевої демократії, запропонувати механізми її розвитку в умовах зростання глобальних викликів та загроз воєнного часу. У першому розділі дисертаційної роботи «Теоретичні засади управління розвитком місцевої демократії» – сформовано предметне поле дослідження проблеми розвитку місцевої демократії – процесу трансформації форм взаємодії держави та громадянина, який через удосконалення принципів, форм, механізмів та інструментів забезпечує підвищення рівня залучення громадян до прийняття рішень на всіх рівнях публічного управління, розкрито сутність проблеми у наукових дослідженнях. На основі комплексного підходу до предмету дослідження систематизовано ключові характеристики й чинники демократизації на різних рівнях та обґрунтовано необхідність їх врахування перед викликами та загрозами воєнного часу. Розкрито та забезпечено розвиток понятійно-категоріального апарату предмету дослідження: сформульовано авторське тлумачення понять «демократія», «місцева демократія», «розвиток місцевої демократії». Визначено роль місцевої демократії у реформуванні системи публічного управління на різних рівнях публічного управління, а також в контексті глобального управління та реалізації Цілей сталого розвитку. Досліджено питання сприяння розвитку місцевої демократії через децентралізацію з боку міжнародних організацій. Уточнено положення концепції розвитку місцевої демократії, які визначають функції громадянська і громади, процедури обговорення проблем, політичну освіту, ефективність урядування, територіальні координати діяльності, матеріально-фінансову основу діяльності. Розкрито сутність дії механізмів розвитку місцевої демократії на основі врахування цільового характеру використання, складної будови, комплексної взаємодії елементів, залежності від умов, динаміки змін. Сформовано концептуальні положення функціонування ефективних механізмів розвитку місцевої демократії, які розглядаються як сукупність алгоритмів здійснення процедур залучення громадян до управління, що формуються під дією правових, організаційних, економічних і соціальних умов, які у взаємодії забезпечують позитивний цільовий результат в сфері розвитку місцевої демократії – підвищують вплив громадянського суспільства на прийняті рішення. Систематизовано методи моніторингу місцевої демократії з урахуванням необхідності вивчення не тільки виключно місцевої демократії, а також тих умов, які сприяють її розвитку. Розглядаються характеристики та наводяться приклади методів вимірювання демократії в країні, методів моніторингу політичних систем, методів моніторингу демократичності публічного управління та методів аналізу місцевої демократії. Уточнено інструменти та цілі оцінювання місцевої демократії; визначено основні напрями аналізу місцевого управління. Суттєвий акцент у дослідженні зосереджено на методах вимірювання місцевої демократії, це надає змогу дослідити демокрaтичний характер місцевого урядування, міцність та якість місцевої демократії, рівень використання е-технологій. Розроблено алгоритм багаторівневого аналізу впливу демократії на економічні процеси. У другому розділі «Система та механізми розвитку місцевої демократії в сучасній Україні» – розглянуто питання щодо розбудови місцевої демократії в Україні з позицій використання механізмів розвитку та врахування зарубіжного досвіду. Запропоновано принципи управління розвитком місцевої демократії, які обґрунтовано на основі систематизації відповідних нормативних документів та принципів європейського й міжнародного рівня, зокрема принципи прозорості та підзвітності, ефективності та результативності, пріоритетності, конвергенції інтересів та компетентності, які мають бути імплементовані в Україні у повній мірі, дозволять використати європейський досвід розвитку демократії та посилять позиції України в контексті інтеграції до ЄС. Розкрито особливості розвитку місцевої демократії в контексті демократизації в умовах різних типів режимів країн світу, а також моделей місцевого самоврядування. Зазначено зниження рівня розвитку демократії в Україні в 2022 році загалом та за такими складовими як виборчий процес та плюралізм, цивільні свободи, причиною чого стала війна. Декларативний та фрагментарний характер розвитку демократії в Україні пояснюється невідповідністю реформ критеріям реальної демократизації. Досліджено особливості процесу децентралізації у різних країнах, який є основою розбудови місцевого самоврядування та розвитку місцевої демократії. Відповідно до сформованих у країнах світу в результаті децентралізації моделей субнаціонального управління (одно-, дво- та трирівневої) здійснюється розподіл державних витрат. Наведено аргументацію щодо впливу рівня децентралізації на економічний розвиток країни, зокрема на рівень капітальних видатків, використання яких на регіональному та місцевому забезпечує реалізацію інвестиційних проєктів, пов’язаних з будівництвом та реконструкцією інфраструктури. Серед позитивних ефектів децентралізації в частині розвитку місцевої демократії слід вказати: підвищення прозорості та підзвітності, забезпечення розширення участі громадян у прийнятті рішень; порівняно кращий рівень врахування потреб громадян через належне ресурсне забезпечення. Демократизація в Україні відбувається за варіантом «затягнутого» переходу, що було зумовлено збереженням негативних характеристик попередньої моделі, низьким рівнем мотивації до системних реформ політичних еліт та низьким рівнем залучення громадян. Незважаючи на реалізацію низки проєктів та ініціатив українських та міжнародних організацій щодо розвитку місцевої демократії спектр інструментів розвитку не набув належного поширення. Виокремлено основні виклики розвитку місцевої демократії під час війни, серед яких виклики адаптації, міграційні та фінансові виклики, функціональні та бюрократичні виклики, виклики сталого розвитку. Ключовим обмеженням діяльності територіальних громад є втрати: демографічні, матеріальні, економічні та фінансові. Позитивним результатом проведених реформ з децентралізації названо високий рівень самостійності місцевої влади у питаннях реагування на виклики військового часу, однак на корупційні скандали та несумлінну поведінку посадових осіб місцева демократія не завжди має інструментарії протидії. У третьому розділі «Перспективні напрями імплементації інноваційних механізмів розвитку місцевої демократії» – запропоновано застосування стратегічного, динамічного, інтегрованого та комплексного підходу до розвитку демократії, що дозволить сформувати концептуальну основу подальших реформ та сприятиме створенню умов для імплементації інноваційних механізмів місцевої демократії. Визначено ключові напрями подальших реформ щодо розвитку місцевої демократії з урахуванням європейського та північноатлантичного векторів розвитку України, необхідності формування драйверів економічного зростання в регіонах, завдань подальшої децентралізації та процесів включення до глобальної мережі міжнародних організацій сприяння демократії, розвитку громадських організацій та громадянського суспільства. Обґрунтовано умови та аргументовано доцільність ефективного використання таких механізмів місцевої демократії як місцеві вибори, місцевий референдум, громадський бюджет, громадські слухання. В якості стратегічного орієнтиру розбудови громадянського суспільства в контексті розвитку місцевої демократії запропоновано перехід від традиційної парадигми залучення громадян, яка передбачає прямий діалог уряду та конкретного громадянина через низку заходів, зокрема: громадських слухань, громадської «освіти», виборів, опитування та письмових коментарів до пропозицій, тощо, до концепції мережевої взаємодії для залучення громадян, де представлені різноманітні інститути громадянського суспільства (громадські організації, неурядові організації, профспілки, громадські рухи, незалежні ЗМІ, аналітичні центри, університети, а також соціальні та релігійні групи), які у взаємодії з публічними організаціями сприяють розбудові соціального та інтелектуального капіталу, інституційної спроможності та адаптивності до змін суспільства в цілому. Обґрунтовано призначення та складові механізмів громадської участі у зміцненні демократії на загальнодержавному та локальному рівнях. Визначено призначення основних форм залучення громадськості, зокрема інформування, консультування, залучення, співпраці та розширення можливостей, які у сукупності дозволять створити умови для системної взаємодії між громадськістю та урядом. Систематизовано переваги/недоліки та умови використання таких механізмів участі громадян: громадські консультативні групи; муніципальне стратегічне планування; соціальний моніторинг; державно-приватне партнерство; публічні (громадські) зустрічі; управлінські мережі залучення громадян. Серед інноваційних механізмів запропоновано використовувати такі механізми як місцева група дій, дорадчі міні-пабліки, панелі спільнот, громадські журі, відкриті громадські простори (хаби). Досліджено вплив цифрових трансформацій та інформаційного перенасичення діяльності органів місцевого самоврядування на ефективність управління, що потребує використання нових технологій. Штучний інтелект є потенційно важливим інноваційним інструментом для трансформації процесів державного управління в контексті підвищення ефективності місцевої демократії. Узагальнено позитивні та негативні ефекти використання штучного інтелекту в процесі місцевого управління. Окреслено основні сфери застосування штучного інтелекту в процесі розвитку місцевої демократії, е-демократії та електронного урядування. Розроблено авторську концепцію управління розвитком місцевої демократії через використання інноваційних механізмів, зокрема таких, як громадські консультативні групи, муніципальне стратегічне планування, соціальний моніторинг, державно-приватне партнерство, публічні (громадські) зустрічі, управлінські мережі залучення громадян, що надає змогу забезпечити постійний діалог та спілкування між обраними посадовцями та громадянами, забезпечуючи безперервний потік інформації для прийняття обґрунтованих рішень відповідно до реальних потреб.
Інноваційні механізми розвитку місцевої демократії
Keywords: демократія; місцева демократія; партисипативна демократія; демократизація; сталий розвиток; принципи; інноваційні механізми; інструменти; публічне управління; прийняття рішень; партнерство; консультації; місцеве самоврядування; децентралізація; реформи; громадянське суспільство; залучення громадян; е-демократія; democracy; local democracy; participatory democracy; democratization; sustainable development; principles; innovative mechanisms; tools; public administration; decision-making; partnership; consultations; local self-government; decentralization; reforms; civil society; citizen involvement; e-democracy